Cost-benefit analysis of ballast water treatment for three major port clusters in China: evaluation of different scenario strategies - Nie, Anwei; Wan, Zheng; Shi, ZhuangFei; Wang, Zhaojun (Frontiers in Marine Science, 2023)
Introduction The expansion of maritime trade has led to the introduction of invasive species into aquatic ecosystems through ballast water discharge. China, being a major player in global trade and manufacturing, has experienced negative impacts on its coastal ecosystems and marine biodiversity. Methods This study examines the cost‒benefit trade-offs of ballast water management policies for major port clusters in China and other global ports. This paper evaluates compliance costs for individual vessels and fleets under different policy scenarios and ballast water treatment system (BWTS) installation strategies. Results The onboard BWTS installation strategy appears to be more cost-effective under the existing International Maritime Organization (IMO) policy. However, with stricter global discharge requirements or a substantial increase in BWTS capital and operating costs, strategies based on port location could prove more beneficial due to potential economies of scale. Notably, ships with high ballast water discharge volumes, like bulk carriers, are potentially better equipped to cope with future policy shifts. In the face of stricter regulations in China, projected annual compliance cost increases range from $456 million (cost data based on China) to $1.205 billion (cost data based on US). Discussion Policymakers are advised to adopt a comprehensive view of ballast water management policies, taking into account the trade-offs between compliance costs and environmental risks. Other essential factors, such as advancements in BWTS technology, fuel consumption, emissions, and maintenance costs, also demand careful consideration in policy development.